A systematic review and meta-analysis of postmastectomy radiation therapy on prepectoral versus subpectoral breast reconstruction - Zheng, Caihong; Liu, Jiameng; Wen, Yahui; Lin, Shunguo; Han, Hui; Xu, Chunsen (Frontiers in Surgery, 2023)
Background Prepectoral breast reconstruction has once again appealed, which attributes to the introduction of acellular dermal matrices (ADMs) and mesh. Postmastectomy radiation therapy (PMRT), meanwhile, is crucial in the whole course of treatment for breast cancer patients with lymph node-positive. The impact of PMRT on outcomes after prepectoral breast reconstruction has not been clearly defined to date. This study aimed to compare the impact of PMRT on outcomes after prepectoral vs. subpectoral breast reconstruction. Methods A comprehensive research on databases including PubMed, Embase, and Cochrane libraries was performed to retrieve literature pertaining to prepectoral breast reconstruction from database inception to October 2021. All included studies evaluated the impact of PMRT on outcomes after breast reconstruction. Only studies comparing patients who underwent prepectoral breast reconstruction with a control group who underwent subpectoral breast reconstruction were included. Data were analyzed using RevMan version 5.2. Results A total of 4 studies were included in the meta-analysis, with a total of 394 breasts. In the setting of postmastectomy radiation therapy, 164 breasts were reconstructed with a prepectoral approach, whereas the remaining 230 breasts underwent subpectoral reconstruction. Overall, outcomes between PBR and SBR was no statistical significance in the overall complications (OR: 1.30, 95% CI: 0.35–4.85), infection (OR: 1.62, 95% CI: 0.90–2.91), seroma (OR: 1.60, 95% CI: 0.48–5.27), skin flap necrosis (OR: 0.77, 95% CI: 0.17–3.45), hematoma (OR: 0.38, 95% CI: 0.10–1.41), wound dehiscence (OR: 0.82, 95% CI: 0.36–1.85). But, included studies lacked data about the patient quality of life and satisfaction with the outcome of the reconstructed breast. Conclusions In the setting of postmastectomy radiation therapy, prepectoral breast reconstruction is a safe and effective option.